Cultural organization, working environment, compensation, and employee performance: the commitment of organization as intervening variable - Titien Tryani; Irvandi Gustari; Tabroni; Andi Amri (Universitas Negeri Padang, 2021)
This study aims to find the effect of the independent variables on the dependent variable through intervening variables. The population in this study was 529 people, all permanent employees of PT. Kedaton Mulia Primas. The results of data management using the slovin formula can be concluded that the number of samples in this study is part of the number of permanent employees of 84 people. There are five types of variables that will be used in this study organizational culture (X1), work environment (X2), compensation (X3), performance (Y) and organizational commitment (Z). This research uses SEM analysis and Smart PLS version 3.0 application. Partial Least Square (PLS) with a quantitative approach through distributing questionnaires with 65 statements of indicators can be seen from the AVE value Organizational culture 0.624 > 0.5 Valid, Work environment 0.581 > 0.5 valid, Compensation 0.702 > 0.5 valid, Employee Performance 0.702 > 0.5 valid, and Organizational Commitment 0.656 > 0.5 valid, so overall there is a positive effect between variables. Keywords: Organizational Culture, Work Environment, Compensation, Performance, Organizational Commitment